1988
DOI: 10.1073/pnas.85.12.4118
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of didemnin B, an antiviral and cytotoxic depsipeptide.

Abstract: Comparison with the structure of cyclosporin A shows distinct stereochemical differences between the two molecules. It is suggested that didemnin B and cyclosporin A are unlikely to have a common receptor binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 11 publications
4
68
0
Order By: Relevance
“…Both NMR 33 and X-ray diffraction 34 studies have shown a highly asymmetric shape for DB, with the macrocycle resembling a twisted figure "8" (Figure 4). The six residues making up the depsipeptide ring structure (isostatine (Ist 1 ), 2-(R-hydroxyisovaleryl) propionate (Hip 2 ), leucine (Leu 3 ), proline (Pro 4 ), N,Odimethyltyrosine (Me 2 Tyr 5 ), and threonine (Thr 6 )) have the L configuration, whereas the linear peptide attached to this latter amino acid contains N-methyl-D-leucine (MeLeu 7 ) and lactylproline (Pro 8 -Lac 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both NMR 33 and X-ray diffraction 34 studies have shown a highly asymmetric shape for DB, with the macrocycle resembling a twisted figure "8" (Figure 4). The six residues making up the depsipeptide ring structure (isostatine (Ist 1 ), 2-(R-hydroxyisovaleryl) propionate (Hip 2 ), leucine (Leu 3 ), proline (Pro 4 ), N,Odimethyltyrosine (Me 2 Tyr 5 ), and threonine (Thr 6 )) have the L configuration, whereas the linear peptide attached to this latter amino acid contains N-methyl-D-leucine (MeLeu 7 ) and lactylproline (Pro 8 -Lac 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…The six residues making up the depsipeptide ring structure (isostatine (Ist 1 ), 2-(R-hydroxyisovaleryl) propionate (Hip 2 ), leucine (Leu 3 ), proline (Pro 4 ), N,Odimethyltyrosine (Me 2 Tyr 5 ), and threonine (Thr 6 )) have the L configuration, whereas the linear peptide attached to this latter amino acid contains N-methyl-D-leucine (MeLeu 7 ) and lactylproline (Pro 8 -Lac 9 ). 2,34 The only transannular hydrogen bond (Ist 1 -NH‚‚‚OdC-Leu 3 ) that has been described in these experimental structures of DB, as well as in the crystal structure of DA 35 and in the solution structure of dehydrodidemnin B (aplidine), 36 is maintained during the MD simulations in water, as is the Leu 3 -NH‚‚‚OdC-MeLeu 7 hydrogen bond that binds the linear chain to the cyclic backbone. In contrast, the hydrogen bond established within the linear part of DB (Thr 6 -NH‚‚‚OdC-Lac 9 ) is overtly disrupted by competing interactions with water molecules (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations